The effect of a particle–matrix interface on the Young's modulus of Al–SiC composites. (January 2016) - Krizik, Peter; Balog, Martin; Matko, Igor; Svec, Peter; Cavojsky, Miroslav; Simancik, Frantisek
In order to improve the Young's modulus of Al–SiC composites, the matrix-reinforcement interface was modified via chemical reactions between the Al matrix and SiC particles. To prepare diverse interfaces, various types of composites were fabricated using the direct hot extrusion of Al-based powder mixtures containing 30 vol% untreated or oxidized SiC particles. The extruded composites were subjected to different annealing treatments. A detailed microstructural characterization of the Al–SiC interfacial regions was performed. The effect of the interface on the Young's modulus and on the other mechanical properties of the composites was systematically investigated. Depending on the interface quality, the Young's modulus of the composites can be varied over the range of 88–121 GPa. The results proved the importance of a stiff phase—comparable to SiC stiffness at the interface, which leads to the SiC particles contributing more effectively to the increase in the composite Young's modulus. Conversely, the segregation of liberated Si at SiC interface led to decrease of composites Young's modulus.